Values and technology in architecture - the impact and vulnerability (Journal of Engineering, 2015)
Technology is an important factor for achieving architecture as an impact and vulnerability. It represents one of the significant elements in creating the intellectual framework, as well as having its own intellectual breakdown, while values constitute the most important and obviously factor of the community's intellectual. Research aims was determined accordingly by: investigating the role and impact of values and their relationship to technology in architecture.In this context, the research investigated values and technology in architecture, through discussing their aspects and dimensions in architecture. In the context of values, the research discussed their concept and the related ones to have a concrete definition, and discussed manifestations in terms intellectual and social system represented by value's judgment and value's system, that  creating the most important factor for the differentiation communities, which were leading to the study of values in architecture. In this context, the research identifies trends of values in architecture to determine and adopt the private values-oriented in architecture.In the other hand, the research discussed the concept of technology, its impact on the architecture through dealing with architectural technology and its dimensions according to the context.  A focus was made on the intellectual dimension, which lies under the physical aspect of the technology. Then a convergence technology utilization and the expressive aspects was made within an input and output of architectural practice which implemented on selected projects. A set of conclusions was achieved regarding the theoretical research framework and the case study as well.